Cloud connected smart home gas cylinder platform based wifi control - C.R. Balamurugan; P. Vijayakumar (Institute of Advanced Engineering and Science, 2019)
Gas sensing technology has become topical research work for quite some time and we also want to protect our home asserts from any kind of hazards. In this work we take an overview on how to protect our home from fire and its safety issues based on wireless sensor network using wifi and cloud technologies. It also showcases the research done on the detection mechanism of leakage of domestic cooking gas at ambient condition. It can detect the fire, leakage of gas or smoke and sends an auto-generated email remotely to intimate the owner. We survey and examine the existing work in security system and its applications.